Renewable Electricity Policy and Market Integration - Thomas Tangerås (Research Institute of Industrial Economics (IFN), 2013)
I analyze renewable electricity policy in a multinational electricity market with transmission investment. If national policy makers choose support schemes to maximize domestic welfare, then a trade policy motive arises operating independently of any direct benefit of renewable electricity. The model predicts electricity importing (exporting) countries to choose policies which reduce (increase) electricity prices. A narrow pursuit of domestic objectives distorts transmission investment, thereby market integration, below the efficient level. Distortions cannot be corrected by imposing national renewable targets alone. Instead, subsidies to transmission investment and a harmonization of and reduction in the number of policy instruments can improve welfare.
Keywords: D23; F15; Q48; Q56; 330; Market integration; Renewable electricity; Trade policy; Transmission investment